Plasma exchange therapy in refractory inflammatory myopathy with anti-signal recognition particle antibody: a case series - Zhang, Hao; Sun, Yue; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Hu, Qiongyi; Jia, Jinchao; Wang, Mengyan; Liu, Tingting; Zhou, Zhuochao; Yang, Chengde; Chi, Huihui; et al. (Rheumatology (Oxford, England), 2022)
Abstract Objectives To explore the efficacy of plasma exchange (PE) therapy in refractory idiopathic inflammatory myopathy (IIM) patients with positive anti-signal recognition particle (SRP) antibody. Methods Nine refractory IIM patients with positive anti-SRP antibody were enrolled, who received PE therapy at Ruijin Hospital from October 2017 to December 2020. The clinical manifestations, laboratory tests, chest CT and lower extremity MRI images before and after PE therapy were compared. The treatment response was evaluated by the 2016 ACR/EULAR myositis response criteria. Results A total of 88.9% (8/9) of subjects had achieved improvement by 3 weeks after PE therapy, with 55.6% (5/9) minimal improvement and 33.3% (3/9) moderate improvement. There were statistically significant improvements between baseline and after PE therapy at 3 weeks on the core set measures: physician global activity, patient global activity, HAQ, manual muscle testing (MMT), extramuscular disease activity, and muscle enzymes activity including creatine kinase (CK), lactate dehydrogenase (LDH), aspartate transaminase (AST), except for alanine transaminase (ALT). Moreover, the chest CT showed regression of ground glass opacities and irregular linear opacities after PE therapy in four patients with interstitial lung disease. The MRI images of lower extremity in four patients showed reduction of muscle oedema after the therapy. Conclusion PE therapy is effective for refractory IIM patients with positive anti-SRP antibody. It should be considered as an alternative treatment for those patients who are resistant to the combined therapy of glucocorticoids and immunosuppressive agents.